Beyond Ritual Practice: Moral Value Internalization through Dawn Halaqah in Islamic Boarding Schools - Hasni Noor; Murdan Murdan; Muhdi Muhdi; Erni Susilawati; Galuh Nashrulloh Kartika MR; Suraijiah Suraijiah (Nazhruna: Jurnal Pendidikan Islam, 2026)
Morals are the primary foundation for students' character in Islamic boarding schools, but modern challenges, such as globalization and the development of information technology, may weaken the internalization of moral values. In this case, the dawn halaqah activity at the Darul Ilmi Banjarbaru Islamic Boarding School is a vital strategy to instill moral values through direct experience, material appreciation, and the example of the supervisors. This research aims to examine the process of internalizing moral values through dawn halaqah as a medium for students' character development. The approach used is a phenomenological qualitative approach, with data collected through in-depth interviews with ustaz, pesantren administrators, and students, as well as participatory observation and documentation. Data analysis is carried out inductively through the stages of reduction, presentation, and conclusion drawing. The results of the study show that dawn halaqah plays a significant role in shaping the attitudes and behaviors of students, including honesty, tawadhu’, responsibility, patience, discipline, tolerance, and emotional control, thereby creating a harmonious and conducive pesantren environment. The internalization process occurs through regular habituation, spiritual reflection, and the example of the supervisor, strengthening spirituality and building students' emotional and social maturity. These findings confirm the effectiveness of routine religious activities as a medium for character development and show that a hands-on and exemplary approach can strengthen the internalization of moral values. The implications of this research can serve as a basis for developing character education strategies in other Islamic boarding schools and religious education institutions, as well as guide teachers in designing activities that are more contextual, systematic, and oriented towards the formation of a complete character. The uniqueness of this study lies in the discovery that the intensity of student involvement in the dawn halaqah is a key factor that directly accelerates the internalization of moral values. This finding has not been widely reported in previous research.